2015
DOI: 10.1590/0101-60830000000062
|View full text |Cite
|
Sign up to set email alerts
|

A psychiatric perspective view of bariatric surgery patients

Abstract: Background: Bariatric surgery is the only procedure that has significant results in weight loss and improvements in medical comorbidities in morbid obese patients. Severely obese patients are also associated with a higher prevalence of psychiatric disorders and poor quality of life. Objective: To evaluate specific areas of psychopathology in individuals undergoing bariatric surgery. Methods: A review of the literature was conducted from January 2002 to March 2014 by researching PubMed database using the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 86 publications
0
3
0
2
Order By: Relevance
“…O Longitudinal Assessement of Bariatric Surgery segue 199 pacientes submetidos ao bypass gástrico, com melhora nos escores de ansiedade e de distúrbios alimentares, entretanto não houve queda nos escores de depressão ou no uso de medicação psiquiátrica (KALARCHIAN et al, 2017). Outro estudo levanta a hipótese de que os benefícios psiquiátricos e psicológicos da cirurgia bariátrica podem ser fugazes, limitados aos primeiros anos de cirurgia e que possa haver piora da saúde mental nesses pacientes (BRANDÃO et al, 2015) Neste trabalho, observou-se resultados compatíveis com a literatura ao comparar pacientes operados e não operados: os primeiros possuem menor IMC, melhor escore de qualidade de vida no componente físico e maior percentual de pacientes com sintomas de ansiedade e de depressão. Os dois grupos de pacientes operados também apresentaram escores estatisticamente semelhantes entre si, mas inferiores aos da população no aspecto mental do SF-36, autoestima, ansiedade e depressão.…”
Section: Discussionunclassified
“…O Longitudinal Assessement of Bariatric Surgery segue 199 pacientes submetidos ao bypass gástrico, com melhora nos escores de ansiedade e de distúrbios alimentares, entretanto não houve queda nos escores de depressão ou no uso de medicação psiquiátrica (KALARCHIAN et al, 2017). Outro estudo levanta a hipótese de que os benefícios psiquiátricos e psicológicos da cirurgia bariátrica podem ser fugazes, limitados aos primeiros anos de cirurgia e que possa haver piora da saúde mental nesses pacientes (BRANDÃO et al, 2015) Neste trabalho, observou-se resultados compatíveis com a literatura ao comparar pacientes operados e não operados: os primeiros possuem menor IMC, melhor escore de qualidade de vida no componente físico e maior percentual de pacientes com sintomas de ansiedade e de depressão. Os dois grupos de pacientes operados também apresentaram escores estatisticamente semelhantes entre si, mas inferiores aos da população no aspecto mental do SF-36, autoestima, ansiedade e depressão.…”
Section: Discussionunclassified
“…Among the factors that we did analyze, however, we were unable to find any association between years of education and female sex with anxiety; this could be attributed to the fact that our sample had a high proportion of female participants. A study conducted in Portugal concluded that the outcomes of bariatric surgery have a tendency to be related to the presence of depression [32]. Preoperative screening and treatment of anxiety and depression could add to the efficacy and amplify weight loss in patients after surgery, enhancing their quality of life in a more continuous manner.…”
Section: Discussionmentioning
confidence: 99%
“…A review article by Brandao et al [3] revealed that 20%-56% of preoperative bariatric patients have a current psychiatric diagnosis. Moreover, the authors pointed out that major depressive disorder is the most frequent condition, followed by social phobia, anxiety disorders, somatization, hypochondria, and obsessive-compulsive disorder [3].…”
Section: Introductionmentioning
confidence: 99%
“…A review article by Brandao et al [3] revealed that 20%-56% of preoperative bariatric patients have a current psychiatric diagnosis. Moreover, the authors pointed out that major depressive disorder is the most frequent condition, followed by social phobia, anxiety disorders, somatization, hypochondria, and obsessive-compulsive disorder [3]. Higher BMI [21,34] and increased visceral fat [25] are frequently reported to be associated with depressive symptoms, e.g., in adults with current depression, or a history of diagnosed depression or anxiety [34].…”
Section: Introductionmentioning
confidence: 99%